Difference between revisions of "009B Sample Midterm 2, Problem 5"
Jump to navigation
Jump to search
Line 17: | Line 17: | ||
|- | |- | ||
| | | | ||
− | ::You could use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -2px">u=\tan x.</math> Then, <math style="vertical-align: -5px">du=\sec^2(x)dx.</math> | + | ::You could use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -2px">u=\tan x.</math> Then, <math style="vertical-align: -5px">du=\sec^2(x)dx.</math> Thus, |
|- | |- | ||
| | | | ||
− | :: | + | ::<math>\begin{array}{rcl} |
+ | \displaystyle{\int \sec^2(x)\tan(x)~dx} & = & \displaystyle{\int u~du}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{u^2}{2}+C}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{\tan^2x}{2}+C.}\\ | ||
+ | \end{array}</math> | ||
|} | |} | ||
Line 28: | Line 34: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |First, we write | + | |First, we write |
|- | |- | ||
− | |Using the trig identity <math style="vertical-align: -5px">\sec^2(x)=\tan^2(x)+1</math> | + | | |
+ | ::<math style="vertical-align: -13px">\int \tan^4(x)~dx=\int \tan^2(x) \tan^2(x)~dx.</math> | ||
+ | |- | ||
+ | |Using the trig identity <math style="vertical-align: -5px">\sec^2(x)=\tan^2(x)+1,</math> we have | ||
+ | |- | ||
+ | | | ||
+ | ::<math style="vertical-align: -5px">\tan^2(x)=\sec^2(x)-1.</math> | ||
|- | |- | ||
− | |Plugging in the last identity into one of the <math style="vertical-align: -5px">\tan^2(x)</math> | + | |Plugging in the last identity into one of the <math style="vertical-align: -5px">\tan^2(x),</math> we get |
|- | |- | ||
− | | | + | | |
+ | ::<math>\begin{array}{rcl} | ||
+ | \displaystyle{\int \tan^4(x)~dx} & = & \displaystyle{\int \tan^2(x) (\sec^2(x)-1)~dx}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\int \tan^2(x)\sec^2(x)~dx-\int \tan^2(x)~dx}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\int \tan^2(x)\sec^2(x)~dx-\int (\sec^2x-1)~dx.}\\ | ||
+ | \end{array}</math> | ||
|- | |- | ||
|using the identity again on the last equality. | |using the identity again on the last equality. | ||
Line 42: | Line 61: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |So, we have <math style="vertical-align: -13px">\int \tan^4(x)~dx=\int \tan^2(x)\sec^2(x)~dx-\int (\sec^2x-1)~dx</math> | + | |So, we have |
+ | |- | ||
+ | | | ||
+ | ::<math style="vertical-align: -13px">\int \tan^4(x)~dx=\int \tan^2(x)\sec^2(x)~dx-\int (\sec^2x-1)~dx.</math> | ||
|- | |- | ||
− | |For the first integral, we need to use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -5px">u=\tan(x)</math> | + | |For the first integral, we need to use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -5px">u=\tan(x).</math> Then, <math style="vertical-align: -5px">du=\sec^2(x)dx.</math> |
|- | |- | ||
|So, we have | |So, we have | ||
|- | |- | ||
− | | | + | | |
+ | ::<math style="vertical-align: -13px">\int \tan^4(x)~dx=\int u^2~du-\int (\sec^2(x)-1)~dx.</math> | ||
|} | |} | ||
Line 56: | Line 79: | ||
|We integrate to get | |We integrate to get | ||
|- | |- | ||
− | | | + | | |
+ | ::<math>\begin{array}{rcl} | ||
+ | \displaystyle{\int \tan^4(x)~dx} & = & \displaystyle{\frac{u^3}{3}-(\tan(x)-x)+C}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{\tan^3(x)}{3}-\tan(x)+x+C.}\\ | ||
+ | \end{array}</math> | ||
|} | |} | ||
Revision as of 14:03, 18 April 2016
Evaluate the integral:
Foundations: |
---|
Recall: |
1. |
2. |
How would you integrate |
|
|
Solution:
Step 1: |
---|
First, we write |
|
Using the trig identity we have |
|
Plugging in the last identity into one of the we get |
|
using the identity again on the last equality. |
Step 2: |
---|
So, we have |
|
For the first integral, we need to use -substitution. Let Then, |
So, we have |
|
Step 3: |
---|
We integrate to get |
|
Final Answer: |
---|